Prevalence of discospondylitis and association with congenital vertebral body malformations in English and French bulldogs - Nick Grapes; Simon Bertram; Rita Gonçalves; Steven De Decker (Journal of Veterinary Internal Medicine)
Abstract Background Limited current information exists regarding discospondylitis within breeds commonly affected by congenital vertebral body malformations. Hypothesis/Objectives Report the prevalence of discospondylitis in English and French bulldogs and investigate for possible associations of discospondylitis with congenital vertebral body malformations. Animals 108 client‐owned dogs. Methods Retrospective multi‐institutional study between June 2010 and 2020. Cases with a diagnosis of discospondylitis on computed tomography (CT) or magnetic resonance imaging (MRI) and complete medical records included. Signalment, discospondylitis location, presence of congenital vertebral body malformations, and the site of maximal kyphosis were recorded. Results The prevalence of discospondylitis was 3.4 (1.6‐6.7, 95% confidence interval [CI]) times higher in French bulldogs (P < .001) and 4.3 (1.7‐9.8, 95% CI) times higher in English bulldogs (<.001), compared with the overall hospital cohort. One or more vertebral malformations were present in 12 French bulldogs (92.3%), 6 English bulldogs (75.0%), and 1 “other” breed dog (1.1%). Discospondylitis was diagnosed adjacent to congenital vertebral body malformations in 12 (80%) intervertebral discs in French bulldogs and 5 (50%) intervertebral discs in English bulldogs. The median age at presentation was significantly younger in French bulldogs (1.1 years; range, 0.5‐9.2 years) and English bulldogs (1.0 years; range, 0.4‐7.0 years), compared with “other” breed dogs (7.3 years; range, 0.3‐14.0 years; both P < .001). Conclusions and Clinical Importance Congenital vertebral body malformations were frequently associated with discospondylitis in French and English bulldogs, with clinical signs commonly encountered at a significantly younger age.